Effect of Location-Based Health Messages on Tourist Knowledge of Travel Disease Risks in Bantimurung National Park, Indonesia - Rahman, Harpiana; Burhan, Zulkhair; Septiyanti, Septiyanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Bantimurung National Park faces health risks such as dengue fever transmission due to its location in an endemic area and the potential for zoonotic transmission through frequent tourist interactions with Macaca maura. The lack of health promotion media related to disease prevention in tourism exacerbates these health risks. This study aims to analyze tourists' knowledge after receiving health messages via location-based advertising, specifically examining whether perceived susceptibility, perceived severity, perceived benefits, and perceived barriers that influence the effectiveness of digital health promotion in high-risk ecotourism environments. Methods: The study used a quantitative approach with a survey method, involving 92 tourist respondents who accessed health information through LBA messages while in the Bantimurung tourist area. The LBA system delivered tailored health messages via mobile devices using geofencing technology within the park area. Data were analyzed using descriptive and inferential statistical tests to measure changes in knowledge levels before and after receiving the information. Results: The results show a significant increase in tourists' knowledge after receiving location-based health messages. Before the intervention, only 23.9% of tourists fully understood disease types, transmission modes, and prevention methods. This figure rose to 67.7% post-intervention, while those with no understanding dropped from 1.1% to 1.0%, and partial understanding decreased from 75.0% to 31.3%. Conclusion: This study concluded that location-based health messages significantly improved tourists' understanding of disease risks and addressed the gap in health promotion in Bantimurung National Park. This research is essential for international health studies, particularly in strengthening health promotion within global health security through the tourism cluster.